I POLICY STRATEGY FOR STUNTING MITIGATION WITHIN THE FRAMEWORK OF ACHIEVING THE SUSTAINABLE DEVELOPMENT GOALS (A STUDY IN BAYUMUNDU VILLAGE, KADUHEJO DISTRICT, PANDEGLANG REGENCY) - Stiawati, Titi; Apriyani , Nurul; Maisaroh, Ima; Framanik, Naniek Afrilla (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Stunting remains a major public health issue hindering the achievement of the Sustainable Development Goals (SDGs), particularly Goal 2 (Zero Hunger) and Goal 3 (Good Health and Well-Being). Previous studies have mostly focused on nutrition and health aspects, while this research addresses the research gap by analyzing policy strategies based on cross-sectoral collaboration at the village level. The purpose of this study is to identify and analyze stunting mitigation policy strategies within the framework of achieving the SDGs in Bayumundu Village, Kaduhejo District, Pandeglang Regency. This research employs Collaborative Governance theory (Ansell & Gash, 2008) and SWOT analysis (Rangkuti, 2018) to map internal–external factors and assess the quality of multi-stakeholder collaboration. The study uses a qualitative descriptive approach, collecting data through interviews, observation, and documentation, with triangulation for data validation. The findings indicate that the main strengths of the strategy are community awareness campaigns and available health infrastructure, while the greatest opportunity comes from national policy and government support. However, weaknesses such as limited community understanding and threats such as socio-economic inequality remain significant challenges. The study concludes that the success of stunting mitigation strategies is strongly determined by actor synergy, facilitative leadership at the village level, and the utilization of national policy opportunities. It recommends strengthening collaborative institutional design and leveraging health technologies to ensure program sustainability